Enhancing Science Literacy Through Local Wisdom: Evidence from the Seuramoe Saentia Learning Model in Aceh - Rita Sari; Maksudin Maksudin; Ibrahim Ibrahim; Sigit Prasetyo; Aninditya Sri Nugraheni; Balqis Wandiri; Siti Patimah; Nor Hasnida Md Ghazali (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2026)
This research is motivated by the low connection between science learning at Madrasah Ibtidaiyah (MI) and the local cultural context of students, which has an impact on the lack of optimal science literacy. Science learning tends to be abstract and textbook-oriented, while the integration of local Acehnese wisdom has not been structured in the learning design. This study aims to (1) analyse the needs of science learning based on local wisdom in Aceh as the basis for the development of the Seuramoe Saentia Learning Model and (2) measure the level of improvement in students' science literacy after the application of the model. The researcher uses a research and development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects, based on the ADDIE model, comprised 138 grade V students from four MI in Langsa City, who were selected through purposive sampling. The research instruments are in the form of observation sheets and science literacy tests (20 pretest questions and 20 posttest questions). The validity of the model was tested using Aiken's V, while the increase in science literacy was analysed using the Wilcoxon Signed Rank Test, effect size, and N-Gain. The results showed that the model had a very high content validity (Aiken's V = 0.96). The Wilcoxon test showed the dominance of positive ratings without a decrease in scores, with an effect size of 0.87 (very large category). An average N-Gain value of 0.72 (high category) indicates a substantial and even increase in science literacy. These findings show that the systematic integration of local wisdom in science learning effectively improves students' science literacy. Implicitly, the Seuramoe Saentia Learning Model can be a strategic alternative in the development of science learning that is contextual, inclusive, and rooted in local culture in madrasas